How Different Albumin-Binders Drive Probe Distribution of Fluorescent RGD Mimetics - Höltke, Carsten; Alsibai, Wael; Grewer, Martin; Stölting, Miriam; Geyer, Christiane; Eisenblätter, Michel; Wildgruber, Moritz; Helfen, Anne (Frontiers in Chemistry, 2021)
The biodistribution of medical imaging probes depends on the chemical nature of the probe and the preferred metabolization and excretion routes. Especially targeted probes, which have to reach a certain protein structure, have to be guided to the tissue of interest. Small molecules have rather short half-lives while antibodies reside inside the organism for a longer period of time and an excretion via kidneys and bladder is faster than a hepatobiliary excretion. Therefore, small hydrophilic probes are excreted very fast with (biological) half-lives of less than two hours, while labelled antibodies circulate for several days. To alter the biodistribution behavior of probes, different strategies have been pursued, including utilizing serum albumin as an inherent transport mechanism for small molecules. We describe here the modification of an existing fluorescent RGD mimetic probe targeted to integrin v3 with three different albumin binding moieties (ABMs): a diphenylcyclohexyl (DPCH) group, a p-iodophenyl butyric acid (IPBA) and a fatty acid (FA) group with the purpose to identify an optimal ABM for molecular imaging applications. All three modifications result in transient albumin binding and a preservation of the target binding capability. Spectrophotometric measurements applying variable amounts of bovine serum albumin (BSA) reveal considerable differences between the compounds concerning their absorption and emission characteristics and hence their BSA binding mode. In vivo the modified probes were investigated in a murine U87MG glioblastoma xenograft model over the course of one week by fluorescence reflectance imaging (FRI) and fluorescence mediated tomography (FMT). While the unmodified probe was excreted rapidly, the albumin-binding probes were accumulating in tumor tissue for at least five days. Considerable differences between the three probes in biodistribution and excretion characteristics were proved, with the DPCH-modified probe showing the highest overall signal intensities, while the FA-modified probe exhibits low but more specific fluorescent signal. In conclusion, the modification of small molecular RGD mimetics with ABMs can precisely fine-tune probe distribution and offers potential for future clinical applications.